2017
DOI: 10.1209/0295-5075/119/17001
|View full text |Cite
|
Sign up to set email alerts
|

Cooper pairs without “glue” in high-T c superconductors: A universal phase diagram

Abstract: The phase diagram of high-Tc cuprates can be understood, without resorting to a boson mode, in terms of a single energy scale ∼ J, the antiferromagnetic (AF) exchange energy at the metal-insulator transition. As a result, holes form a new quantum object, the "pairon", i.e., a pair of holes localized within their local antiferromagnetic environment on the scale of the finite AF correlation length, ξAF . In the incoherent pseudogap phase, above Tc or within the vortex core, the pairon binding energies are distri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 39 publications
2
29
0
Order By: Relevance
“…In previous work we showed that this interaction follows the critical dome and has the value β ∼ 2 k B T c . Moreover, the pairon condensate model matches the phase diagram for a wide range of doping in terms of a single energy scale, J, the exchange energy [22]. Using the gap equation (9), and the energy bands k of cuprates from Markiewicz et al [26], the spectral function of quasiparticles is obtained for any wavevector k. Assuming nearly optimal doping (∆ p (0) = 40 meV, T c = 92 K) the spectral intensity in the AN direction crossing k F is shown in Fig.…”
Section: Pairon Condensationmentioning
confidence: 80%
See 1 more Smart Citation
“…In previous work we showed that this interaction follows the critical dome and has the value β ∼ 2 k B T c . Moreover, the pairon condensate model matches the phase diagram for a wide range of doping in terms of a single energy scale, J, the exchange energy [22]. Using the gap equation (9), and the energy bands k of cuprates from Markiewicz et al [26], the spectral function of quasiparticles is obtained for any wavevector k. Assuming nearly optimal doping (∆ p (0) = 40 meV, T c = 92 K) the spectral intensity in the AN direction crossing k F is shown in Fig.…”
Section: Pairon Condensationmentioning
confidence: 80%
“…In this article, we answer these questions in the framework of the condensation of preformed pairons [22]. To proceed, we calculate the spectral function for cuprates and directly compare the computed energy distribution curves (EDCs) to the ARPES measurements as a function of temperature and angle at the Fermi surface.…”
mentioning
confidence: 99%
“…where p min ≈0.05 is the value at the SC onset and where C = 0.9 for Bi 2 Sr 2 CaCu 2 O 8+δ , as deduced from fits of tunneling data [20]. The critical doping p c ≈ 0.27 is directly related to the pairon size [20]. While the gap energy is analogous to the Cooper pairing between two fermions, the quantity β c arises from an additional four fermion term in the hamiltonian [22] which couples different pair states.…”
Section: Pairon Modelmentioning
confidence: 99%
“…We emphasize the fundamental difference between such a local composite boson as a "preformed" pair and a Cooper pair composed of +k and -k partners. However, the on-site ZR boson also differs significantly from composite inter-site bosons, such as magnetic or lattice bipolarons [21,22] or magnetic "pairons" [23].…”
Section: Charge Triplet Model: S = 1 Pseudospin Formalismmentioning
confidence: 99%